Flowering Plants of Sanjay-Dubri Tiger Reserve, Madhya Pradesh, India - Tiwari, Arjun Prasad; Khanna, K. K.; Dubey, P. C. (Indian Forester, 2019)
The present work on flowering plants of Sanjay-Dubri Tiger Reserve, Madhya Pradesh reveals that a total number of 707 species under 432 genera belonging to 107 families are recorded. Of these, 207 species under 118 genera belongs to 20 families of Monocot and 500 species under 314 genera belongs to 87 families of Dicot. Based on field observations, there are 76 species identified as extremely rare and rare in the present study area.